Second-line treatment of advanced non-small cell lung cancer with paclitaxel and gemcitabine: A preliminary report on an active regimen - Georgoulias, V.; Kourousis, C.; Kakolyris, S.; Androulakis, N.; Dimopoulos M.-, A.; Papadakis, E.; Kotsakis, T.; Vardakis, N.; Kalbakis, K.; Merambeliotakis, N.; Hatzidaki, D. (Seminars in Oncology, 1997)
A phase II study of combination paclitaxel (Taxol; Bristol-Myers Squibb Company, Princeton, NJ)/gemcitabine was conducted in patients with non-small cell lung cancer (NSCLC) who had failed first, line docetaxel- or cisplatin- based chemotherapy. Eligibility criteria included histologically confirmed measurable stage IIIB or IV NSCLC and previous exposure to docetaxel, or cisplatin-based regimens. World Health Organization performance status between 0 and 2, adequate hematologic parameters, and adequate hepatic, renal, and cardiac function. Gemcitabine (900 mg/m2) was given on days 1 and 8 as a 30-minute infusion; paclitaxel (175 mg/m2) was administered on day 8 as a 3-hour infusion after appropriate premedication. Granulocyte colony- stimulating factor (150 μg/m2 subcutaneously) was given on days 9 to 15. Treatment was repeated every 3 weeks until patients experienced disease progression. From October 1995 to December 1996, 26 patients with advanced NSCLC were enrolled (three stage IIIB, 23 stage IV). All 26 patients were assessable for toxicity, and 24 were evaluable for response. Two complete (8%) and five partial (21%) responses were observed, for an overall response rate of 29% (95% confidence interval, 11% to 47%). The median duration of response was 2.5 months and the median survival was 8 months. A median of three courses per patient was administered, and the median interval between courses was 21 days. The median delivered dose was 579 mg/m2/wk gemcitabine and 54.5 mg/m2/wk paclitaxel, corresponding to a relative dose intensity of 0.97 and 0.96, respectively. Grade 314 neutropenia occurred in two patients (8%). Grade 3 conjunctivitis occurred in one (4%) patient and grade 213 neurotoxicity in eight (31%) patients. Grade 314 and grade 2 fatigue occurred in four (15%) and eight (31%) patients, respectively. Other toxicities were mild to moderate. These preliminary results suggest that the paclitaxel/gemcitabine combination is an active and well-tolerated salvage regimen in patients with NSCLC previously treated with docetaxel, or cisplatin-based chemotherapy. The paclitaxel/gemcitabine combination merits further evaluation as first-line treatment.